ALMA and ROSINA detections of phosphorus-bearing molecules: the interstellar thread between star-forming regions and comets. Issue 1 (15th January 2020) - Rivilla, V M; Drozdovskaya, M N; Altwegg, K; Caselli, P; Beltrán, M T; Fontani, F; van der Tak, F F S; Cesaroni, R; Vasyunin, A; Rubin, M; Lique, F; Marinakis, S; et al.
ABSTRACT: To understand how phosphorus (P)-bearing molecules are formed in star-forming regions, we have analysed the Atacama Large Millimeter/Submillimeter Array (ALMA) observations of PN and PO towards the massive star-forming region AFGL 5142, combined with a new analysis of the data of the comet 67P/Churyumov–Gerasimenko taken with the Rosetta Orbiter Spectrometer for Ion and Neutral Analysis (ROSINA) instrument onboard Rosetta . The ALMA maps show that the emission of PN and PO arises from several spots associated with low-velocity gas with narrow linewidths in the cavity walls of a bipolar outflow. PO is more abundant than PN in most of the spots, with the PO/PN ratio increasing as a function of the distance to the protostar. Our data favour a formation scenario in which shocks sputter phosphorus from the surface of dust grains, and gas-phase photochemistry induced by UV photons from the protostar allows efficient formation of the two species in the cavity walls. Our analysis of the ROSINA data has revealed that PO is the main carrier of P in the comet, with PO/PN > 10. Since comets may have delivered a significant amount of prebiotic material to the early Earth, this finding suggests that PO could contribute significantly to the phosphorus reservoir during the dawn of our planet. There is evidence that PO was already in the cometary ices prior to the birth of the Sun, so the chemical budget of the comet might be inherited from the natal environment of the Solar system, which is thought to be a stellar cluster including also massive stars.